Experiments and computational models to characterize a radiofrequency ablation device for the treatment of rhinitis - Chamani, Faraz (Kansas State University, 2019)
Chronic rhinitis is a common health problem described as inflammation of mucous membranes within the nasal cavity. Radiofrequency ablation (RFA) is a minimally invasive therapeutic option for thermal tissue destruction under investigation for treatment of rhinitis. The primary objective of this research is to develop an experimentally validated computational model to guide the design and optimization of RFA devices and systems with application to treating chronic rhinitis. In collaboration with Neurent Medical, we are developing a deployable RFA electrode array for treatment of chronic rhinitis. The impact of RFA device geometry, including electrode length (1.25 mm- 1.75 mm) and inter-pair spacing (3.6 mm- 5 mm), on thermal ablation zones was investigated, and simulation results were experimentally validated by conducting ex vivo experiments. Experimental results indicate that increasing electrode length as well as inter-pair spacing within electrode pairs from 1.25 mm to 1.75 mm, and from 3.6 mm to 5 mm respectively, can double the mean depth of ablation from 2 mm to 4 mm (while causing discrete surface ablation zones following RFA). Furthermore, the effects of different energy delivery strategies, including constant power as well as 30% and 60% duty cycle application on ablation results, were investigated through experiments in ex vivo tissue. Duty cycled energy delivery may prolong the ablation time depending on applied power level. However, in order to achieve sufficiently deep thermal lesions of 4 mm, thermal damage to tissue surface would be inevitable when using either constant or pulsed energy delivery. The impact of blood perfusion on ablation results was assessed with a computational model. The blood flow effect on ablation zones was negligible within the first 5 s of RFA in superficial regions of 0.5 mm distance from the tissue surface, likely due to a fast heating rate within target tissue. In summary, the computational modeling and experimental results presented in this report have identified suitable electrode geometry and energy delivery levels for achieving ablation depths of up to 4 mm in the nasal mucosa. These results support the potential of using a deployable RFA electrode for treatment of chronic rhinitis.
Keywords: Rhinitis; Radiofrequency ablation; Bioheat transfer